Heterogeneity of Tumour Infiltrating Lymphocytes (TILs) in breast cancer and its prognostic significance - Althobiti, Maryam; Aleskandarany, Mohammed A.; Joseph, Chitra; Toss, Michael; Mongan, Nigel; Diez-Rodriguez, Maria; Nolan, Christopher C.; Ashankyty, Ibraheem; Ellis, Ian O.; Green, Andrew R.; Rakha, Emad A. (Wiley, 2018)
Background: Tumour-infiltrating lymphocytes (TILs) in breast cancer (BC) confer prognostic and predictive information. This study aims to assess the spatial and temporal heterogeneity of TILs in BC and its relationship with immune cell subtypes. Method: Immunohistochemically-defined immune cell subtypes; T-cell markers (CD3, CD8, and FOXP3), B-cell marker (CD20) and histiocytic marker (CD68) were evaluated in a large series (n=1,165) of invasive BC. A subset of full-face haematoxylin and eosin (H&E) stained slides were examined for TILs heterogeneity within primary tumours and the corresponding local recurrent carcinomas to report on spatial and temporal TILs heterogeneity. H&E stained sections from multiple tumour blocks (3-4 blocks per case) representing different tumour areas were evaluated to assess TILS inter-slide heterogeneity as well as intra-slide heterogeneity. Both average (AV-TILs) and hotspot (HS-TILs) stromal TILs were assessed. Results: AV-TILs showed association with all immune cell subtypes however; the main component were CD3+ cells (mean number = 55) whereas CD20+cells comprised the least component (the mean number = 13). There was no significant statistical difference between TILs across tumour blocks of the same case (p=0.251 for AV-TILs and p=0.162 for HS-TILs). Triple negative breast cancer (TNBC) showed higher TILs compared with other BC subtypes (p<0.001). High AV-TILs, CD3+, CD8+, and CD20+ cells were associated with longer survival in TNBC (p<0.05). High AV-TILs in recurrent tumours showed significant association with shorter post-recurrence survival (p=0.004). Conclusion: Despite the heterogeneity of immune cell type components, average TILs in one full-face H&E stained section reliably represent whole tumour TILs. TILs were associated with outcome in TNBC as well as provided prognostic significance in recurrent tumour.